Otoacariasis: Clinical Characteristics and Outcome: A Study in Central Part of Nepal - Bhandari, Ramesh; Aryal, Bivek; Bajracharya, Rohita; Kandel, Damodar; Darnal, Chunu; Gurung, Lal Bahadur (Journal of College of Medical Sciences-Nepal, 2025)
Background Tick and mite infestation within the ear canal is Otoacariasis. Tick is found all over the world and more prevalent in tropical and subtropical region like Nepal. Tick causes significant morbidity, economic loss, even mortality in both human and animals so it is public health problem. The aim of this study is to find demographic pattern, to evaluate the clinical presentation, treatment and complications due to tick bite of patients presenting in our hospital. Methods A cross-sectional study was conducted in the Department of ENT-Head and Neck Surgery, Bharatpur Hospital, Bharatpur, Chitwan, Nepal Bharatpur Hospital, Chitwan, Nepal from October 2023 to February 2024. Patients who had presented in ENT OPD or in Emergency with ear symptoms were evaluated by Otolaryngologists. After identifying the exact location of tick, with the help of head light or otoscope, it was grasped by alligator forcep and removed. Results There were 47 cases enrolled in this study. Female (38) outnumbered male (9) with ratio 4.2:1. Age of the patients was 1 through 72 years with mean age 33.14. Most common symptom was pain. Most of the patients were children below 11 years followed by young adults in between 21 to 30 years. Preferred location was posterior wall of external auditory canal (36.17%). Tympanic membrane perforation, facial nerve palsy was not seen in anyone. Systemic tick borne diseases were not seen in any patients. Conclusions Human tick infestation is common in Nepal during dry season. Most patients had pain as presenting symptom. Tick can be removed in OPD without complications. Tick borne systemic diseases were not seen in otoacariasis.